2012
DOI: 10.1007/s10658-011-9930-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between agronomic factors and epidemics of Phytophthora branch canker of citrus in southwestern Spain

Abstract: Phytophthora branch canker, caused by Phytophthora citrophthora, has been an increasing problem in clementine (Citrus reticulata) production in Spain during last years. The disease was particularly severe in the new citrus-growing areas of the southwestern coastal areas in Huelva Province. Recent studies revealed that disease emergence was not related to either genetic drift or host specificity changes in P. citrophthora population. Therefore, the possible association of agronomic factors with the disease was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Captan was the most studied (111 case studies), followed by chlorotalonil (100), metalaxyl (80) and mefenoxam (59). Among the aquatic database, the most studied were chlorotalonil (102) followed by triclosan and epoxiconazole (both 14), captan (12) and tebuconazole (8).…”
Section: General Features Of the Access Databasementioning
confidence: 99%
See 1 more Smart Citation
“…Captan was the most studied (111 case studies), followed by chlorotalonil (100), metalaxyl (80) and mefenoxam (59). Among the aquatic database, the most studied were chlorotalonil (102) followed by triclosan and epoxiconazole (both 14), captan (12) and tebuconazole (8).…”
Section: General Features Of the Access Databasementioning
confidence: 99%
“…Among insecticides (Table 24), the total number of records was 850 for the terrestrial lot (covering 60 compounds in total) and 81 (coming from 13 compounds) for the aquatic. Most represented were chlorpyrifos (124 case studies), fenamiphos (91) and teflubenzuron (50) for the terrestrial lot ( Figure 7); dimethoate (20), pirimicarb (12), aldrin (8), lindane (8) and endosulfan (8) for the aquatic ( Figure 8). Finally, a few chemicals belonging to other minor classes such as acaricides, nematicides, bactericides and plant growth regulators were also included (Table 25): the total number of records related to these other classes was 136 for the terrestrial database and only 3 for the aquatic (all 3 referred to Azocyclotin, an acaricide).…”
Section: Supporting Publications 2012:en-359 33mentioning
confidence: 99%
“…Pruning can also stimulate the effects of nematode infection [58]. Although some works indicate that the pruning of symptomatic branches can control citrus variegated chlorosis [59], some authors consider it impossible to control wood diseases such as virus, bacteria, or fungi diseases through pruning [68][69][70][71][72][73][74][75].…”
Section: Pest and Disease Controlmentioning
confidence: 99%
“…An observational study using multivariable explanatory models was identified as an approach that could quantify productivity impacts in commercial orchards subjected to different management regimes and other factors affecting disease risk. There has been increased interest in applying multivariable models to experimental data (Garrett et al ., ; Scherm et al ., ), but the use of observational studies instead of experimental studies is rare in plant protection research, with only a small number of examples (Dallot et al ., ; Thebaud et al ., ; Vicent et al ., ). However, these methods are widely used in studies of animal health and production (Dohoo et al ., ; Alarcon et al ., ).…”
Section: Introductionmentioning
confidence: 97%